Estimating the proportion of pneumonia attributable to pneumococcus in Kenyan adults: latent class analysis. - Jokinen, J; Scott, J (2010)
BACKGROUND: Community-acquired pneumonia is a common cause of hospitalization among African adults, and Streptococcus pneumoniae is assumed to be a frequent cause. Pneumococcal conjugate vaccine is currently being introduced into childhood immunization programs in Africa. The case for adult vaccination is dependent on the contribution of the pneumococcus to the hospital pneumonia burden. METHODS: Pneumococcal diagnosis is complex because there is no gold standard, and culture methods are invalidated by antibiotic use. We used latent class analysis to estimate the proportion of pneumonia episodes caused by pneumococcus. Furthermore, we extended this methodology to evaluate the effect of antimicrobial treatment on test accuracies and the prevalence of the disease. The study combined data from 5 validation studies of pneumococcal diagnostic tests performed on 281 Kenyan adults with pneumonia. RESULTS: The proportion of pneumonia episodes attributable to pneumococcus was 0.46 (95% confidence interval = 0.36-0.57). Failure to account for the effect of antimicrobial exposure underestimates this proportion as 0.32. A history of antibiotic exposure was a poor predictor of antimicrobial activity in patients' urine. Blood culture sensitivity for pneumococcus was estimated at 0.24 among patients with antibiotic exposure, and 0.75 among those without. CONCLUSIONS: The large contribution of pneumococcus to adult pneumonia provides a strong case for the investigation of pneumococcal vaccines in African adults.